Strategi Penguatan Usaha Ekonomi Petani Kakao oleh Gapoktan Guyub Santoso di Desa Plosorejo Kecamatan Kademangan Kabupaten Blitar - Basyir, Malik Naharul; Jannah, Raudlatul (e-Sospol, 2017)
Abstract The problems faced by farmers in Indonesia still struggling in the weak structure of the network. Where the farmers prefer to depend on kinship relations and chose to run its business outside of the formal organization. The farmers tend to seek own patterns of organizing his business according to their better rational for various reasons. Here, the empowerment and organizing farmers by agents into the formal organizational structure became more important to construct mindset of farmers, so that the farmer can progress towards a better and can sustain development of the national economic. This research used a qualitative method which was located in Gapoktan Guyub Santoso Office and Wisata Edukasi Kampung Coklat in Plosorejo Village, District Kademangan, Blitar. The data were collected through interviews, observation and documentation. The research results showed that: the solidarity and participation of farmers into a farming institution is a key element that supports the success of Gapoktan Guyub Santoso in strengthening the capital and breaking the marketing chain of cocoa beans is too long and much harm to farmers. With the development of agro area through Wisata Edukasi Kampung Coklat also improve the quality and selling value of cocoa farmers and bring the impact of economic improvement of the surrounding community through various business opportunities. This is in accordance with the concept of participation empowerment explained by Craig and Mayo that participatory empowerment is a potential strategy in order to improve economic, social and cultural transformation. Therefore, emphasis should be emphasized on the importance of alternative approaches to development approaches beginning with the local community empowerment process.